2008
DOI: 10.1016/j.cmet.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Glucagon Receptor Is Required for the Adaptive Metabolic Response to Fasting

Abstract: Glucagon receptor (Gcgr) signaling maintains hepatic glucose production during the fasting state however the importance of the Gcgr for lipid metabolism is unclear. We show here that fasted Gcgr-/- mice exhibit a significant increase in hepatic triglyceride secretion and fasting increases fatty acid oxidation (FAO) in wild type (WT) but not in Gcgr-/- mice. Moreover fasting upregulated the expression of FAO-related hepatic mRNA transcripts in Gcgr+/+ but not in Gcgr-/- mice. Exogenous glucagon administration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
218
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(238 citation statements)
references
References 47 publications
17
218
2
1
Order By: Relevance
“…Although glucagon has been reported to inhibit lipid secretion from hepatocytes [33], circulating levels of glucagon were not reduced following sitagliptin administration in our current experiments. Furthermore D-Ala 2 -GIP did not reduce, but actually promoted postprandial triacylglycerol and ApoB-48 secretion.…”
Section: Discussionmentioning
confidence: 48%
“…Although glucagon has been reported to inhibit lipid secretion from hepatocytes [33], circulating levels of glucagon were not reduced following sitagliptin administration in our current experiments. Furthermore D-Ala 2 -GIP did not reduce, but actually promoted postprandial triacylglycerol and ApoB-48 secretion.…”
Section: Discussionmentioning
confidence: 48%
“…NMR isotopomer analyses show that PGC-1␣-KO liver has reductions in fatty acid oxidation, ketogenesis, TCA flux, and gluconeogenesis that mirror those in the FGF21-KO liver (4). Because glucagon and its downstream effector, cAMP, induce PGC-1␣ and gluconeogenic gene expression during the early stages of the fasting response (24,35), we propose that FGF21 maintains the expression of these genes during prolonged fasting and starvation.…”
Section: Discussionmentioning
confidence: 97%
“…In rodents glucagon seems to stimulate Fgf-21 expression in vitro and in vivo [12][13][14][15], and these effects are somewhat augmented by NEFA [15]. However, another study reported that glucagon fails to stimulate hepatic Fgf-21 mRNA expression in rodents [16].…”
Section: Introductionmentioning
confidence: 99%